Stress of medical personel related to specyfic work inthe psychiatric ward - Rejek, Ewa; Szmigiel, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Stress is an integral component of modern man. Also, the stress of professional activity performed. Aim. The study examined psychiatric staff opinion about the stress of their work environment. Material and methods. The study was conducted on a group of 100 people working in varius mental health centers. Results. All respondents said that the specificity of psychiatic causes stress among workers. The most stressful are agressive behavior, suicidal risk and with selfpatients. Stress has significant effects on physical and mental health and social functioning of respondents. Most respondents cope with stress alone or assisted by colleagues. Most often declared ways to combat stress is the favorite leisure, hobby, sport. Conclusions. Employees of psychiatric aware of the existence of stress that accompanies the specifics of their work. They are able to cope with stress and take action to alleviate its effects. Nursing Topics 2015; 23 (4): 515–519